Optimization of the process of Phytoremediation whit Festuca Dolichophylla and ammonium thiosulphate to improve the effectiveness of mercury absorption from soils contaminated whit mercury by mining in the district of Ananea Puno-Peru - Arce Sancho, Siles Nilo (2021)
An environmental liability in Peru is located in Puno, in the district of Ananea, originated by informal mining activities 90 years ago. Phytoremediation was carried out with Festuca Dolichophylla, a plant native to the area, with the assistance of ammonium thiosulfate as an accelerator. Soil samples were extracted from the areas impacted with mercury. The research used a factorial design with the following response variables: the concentration of total mercury (HgT) in soil and plant tissues, and as factors the level of ammonium thiosulfate in the soil and the time of plant growth. The soils of the Ananea-Puno district have neutral pH, elemental mercury constitutes 56% of the total amount of mercury in the soil. THg concentrations in the soil range from 44 to 53 mg/ kg, which is almost 2 times higher than the upper limit for mercury content (24 mg/kg) in extractive soils in Peru. The BAF (Bioaccumulation Factor) obtained was 0.38 in leaves, for 2 g of ammonium thiosulfate per kg of soil, indicating that Festuca Dolichopylla is a non-hyperaccumulator plant. The THg content was reduced in the soil in relation to the initial soil, by 43.67 mg/kg, obtaining an efficiency of up to 82%.